ANALISIS PERHITUNGAN HARGA POKOK JASA PENGIRIMAN DALAM PENETAPAN TARIF PENGIRIMAN BARANG DOMESTIK DENGAN PENDEKATAN VARIABLE COSTING PADA CV. BOGOR LOGISTIC CARGO - Prayogi, Angga Cahya; Kusuma, Indra Cahya; Afif, Muhamad Nur (Jurnal Akuntansi Kompetif, 2025)
Miscalculations of production costs for certain products lead to improper selling prices, which may be too high or too low. Both of these possibilities lead to losses for the company. Conversely, if the selling price is too low, the profit earned by the company will also be low or even a loss. This article will explain how to calculate the cost of production to determine the appropriate selling price. Production costs include elements such as raw material costs, direct labor costs, and factory overhead costs. This research method adopts a qualitative description method, by analyzing the cost of production which is calculated using the variable cost method as the basis for determining the selling price. The results of this study are that when calculating shipping costs to be able to set freight rates at the company, they still misclassify the portion of each cost that affects the total cost of goods received by the company. The purpose of this study is to determine the determination of production costs that apply to CV. Bogor Logistics Cargo. Keywords: Delivery Cost, Variable Costing, Selling Price.